Joint Decomposition of Pure and Socioeconomic Health Inequalities in Quebec - Wu, Qingqing (Université d'Ottawa | University of Ottawa, 2011)
The decomposition of health inequality is important for health care policy making. In this paper, based on the CCHS 2007-2008, we use the measure proposed by Makdissi and Yazbeck (2011), which is associated with the socioeconomic health inequality aversio